Rapid and sensitive detection of dual lung cancer-associated miRNA biomarkers by a novel SERS-LFA strip coupling with catalytic hairpin assembly signal amplification. Issue 10 (24th February 2021) - Cao, Xiaowei; Sun, Yue; Mao, Yu; Ran, Menglin; Liu, Yifan; Lu, Dan; Bi, Caili
Abstract : A novel surface-enhanced Raman scattering-lateral flow assay strip in combination with catalytic hairpin assembly signal amplification has been developed for rapid and sensitive detection of miR-196a-5p and miR-31-5p associated with lung cancer. Abstract : A novel surface-enhanced Raman scattering (SERS)-lateral flow assay (LFA) biosensor in combination with catalytic hairpin assembly (CHA) signal amplification has been developed for the analysis of miR-196a-5p and miR-31-5p associated with lung cancer. In the presence of target miRNAs, two hairpin DNAs self-assembled into double-stranded DNA, making biotin molecules on the surface of Au–Ag nanoshuttles (Au–AgNSs) exposed. Therefore, the target enters the next cycle, while SERS complexes were trapped and concentrated on the different test lines (T1 and T2 lines), strongly amplifying the SERS signals. Through the finite difference time domain method, it was proved that the intense electromagnetic field enhancements provided "hot spots" for SERS in the nanogaps between aggregated Au–AgNSs, making Au–AgNSs exhibit excellent SERS performance. The prepared biosensor enabled rapid, sensitive, specific and simultaneous detection of miR-196a-5p and miR-31-5p. The whole detection time was short (40 min), and the detection limits of miR-196a-5p and miR-31-5p were as low as 1.171 nM and 2.251 nM in phosphate buffer, and were 1.681 nM and 2.603 nM in human serum, respectively. For the high accuracy diagnosis of lung cancer, SERS was successfully applied to quantitatively detect these two miRNAs in clinical serum from lung cancer patients at different stages and healthy subjects. The results of the SERS-LFA method were comparable to those of the real-time polymerase chain reaction. The designed multiple signal amplification SERS biosensor would be a very promising alternative tool for miRNA research in the field of biomedical diagnosis, which is of vital importance in the early detection and prevention of lung cancer.